Weapons and technology of World War II - Chorlton, Windsor (Chicago, Ill. : Heinemann Library, 2002)
Examines the changes in weapons and tactics that impacted the way war was waged during World War II.
Includes bibliographical references (p. 45) and index.
Keywords: World War, 1939-1945 -- Equipment and supplies -- Juvenile literature; World War, 1939-1945 -- Campaigns -- Juvenile literature; Military weapons -- History -- 20th century -- Juvenile literature; World War, 1939-1945 -- Equipment and supplies; Military weapons